ANALISIS KANDUNGAN NITRIT DALAM SOSIS PADA DISTRIBUTOR SOSIS DI KOTA YOGYAKARTA TAHUN 2011 - Nur, Hasna Hayati; Suryani, Dyah (Universitas Ahmad Dahlan, 2012)
Background: Sausage was a snack with raw meat, crushed meat preserved by salting. Nitrateand nitrite salt is one of the preservatives used in meat preservation process to obtain goodcolor and prevent microbial growth. Nitrite as a preservative permitted its use, but keep in mindits use in food in order not to exceed the limits, so it does not negatively impact human health.Permenkes Republic of. 1168/Menkes/Per/X/1999 about food additives limit the maximum useof the preservative nitrite in processed meat product that is equal to 125 mg / kg. Excessiveconsumption of nitrite can cause harm to the wearer, whether they are direct, ie poisoning, orwho are indirect, ie nitrites are carcinogenic. The purpose of this study to determine the contentof nitrite in sausages at sausage distributor in the city of Yogyakarta in 2011.Method: The study was descriptive research laboratory test. The object of this study were 5brand sausage sausage found in a different distributor. Nitrite content analysis conducted by twostages of testing, the test qualitative and quantitative test. Qualitative test performed todetermine whether there is content of nitrite in sausages by using reagents sulfanilat acid-?-naftilamina, while the quantitative tests conducted to determine the levels of nitrite contained inthe sausage with a spectrophotometer. Data analysis results of research done descriptively andare presented in table and narrative.Results: The study of five brands of sausage on the distributor in the city of Yogyakarta showsthat all brands of sausage samples containing nitrite with nitrite levels varied.Conclusion: Of the 5 brands of sausage samples studied, the results showed that one samplehad higher levels of nitrite that does not meet the requirements under Decree No. Permenkes.1168/Menkes/Per/X/1999, namely the brand sausage sample E with higher levels of nitrite of211.294 mg / kg.Keywords: Analysis, sausage, nitrite